Authority control in the bibliographic domain: Digital catalogs - Assumpção, Fabrício Silva [UNESP]; Santos, Plácida Leopoldina Ventura Amorim Da Costa [UNESP]; Zafalon, Zaira Regina (University Library System, University of Pittsburgh, 2017)
In this paper we use a literature review to analyze authority control in digital catalogs. In order to do that, we start with a brief introduction to authority control, we contextualize library automation and the rising of digital catalogs from 1960s, and then we highlight some developments in the history of digital catalogs, such as the development of MAchine-Readable Cataloging (MARC) formats for bibliographic and authority data. After that, we present the Functional Requirements for Authority Data (FRAD) and the Functional Requirements for Subject Authority Data (FRSAD) as a synthesis of the current understanding about authority control. Finally, we describe the data model used in the current digital catalogs and we point out: the presence of authority control in the history of Cataloging, the value of FRAD and FRSAD conceptual models, the coverage of authority records by the Resource Description and Access (RDA), and the importance of the understanding about authority control in the current context of Cataloging.
O controle de autoridade no domínio bibliográfico: Os catálogos digitais1
Keywords: Authority control; Bibliographic catalogs; Descriptive cataloging; Functional requirements for authority data (FRAD); Functional requirements for subject authority data (FRAD); History of cataloging